Putusan Mahkamah Konstitusi No.60/Puu-XXII/2024 Lindungi Hak Konstitusional Warga dan Parpol dalam Pemilihan Kepala Daerah Serentak di Daerah - Alimsyah, Syamsuddin; Syam, Radian (Neolectura, 2024)
Since Indonesia's establishment and independence, the process of filling the seats or positions of Regional Heads has changed many times, starting from the Old Order era, the New Order, and the reform period. These changes are actually in accordance with the needs of the times and not motivated by the interests of maintaining power. The decision of the Constitutional Court (MK) Number 60/PUU-XXII/2024 is right for now. At least it saves democracy from the cartel politics being played by the political elites in the country. The Constitutional Court's decision, which changed the threshold to resemble or almost the same as the requirements for individual candidates, opened the faucet for competition to become even more alive. This includes guaranteeing the constitutional rights of non-parliamentary political parties (without seats) to be able to nominate candidates for Regional Heads who were originally unable to as specified in Article 40 of Law 10 of 2016 concerning Pilkada. However, for the sustainability of democracy in the future, the author views that this decision is not optimal or still leaves problems. In the future, the implementation or application of a threshold or minimum requirement of support for the nomination of candidates for Regional Heads and even the President is no longer appropriate. In the future, an open nomination system should be applied, in which all political parties participating in the elections that pass the KPU verification are automatically entitled to propose candidates for Regional Heads. Some countries that adhere to the Presidential system do not recognize the term threshold. America, Brazil, Peru, Mexico, Colombia, and Kyrgyzstan.